Método para compressão de imagens digitais fundamentado em procedimentos de Huffman e Wavelets - Betetto, Luciana Aparecida de Oliveira (Universidade Federal de São Carlos, 2005)
The amount of transmitted, stored and accessed information by computers have been growing exponentially on the last decades. Two factors have contributed to this effect, one is the appearing of the multimedia systems with its variety of applications. The other is all that fact that nowadays computers not only operate texts and numbers but sounds, images, movies and virtual reality. Inside this scenario of new reality, we can also find, the development and the growth of the internet availability (World Wide Web), an interactive and multimedia system based on information, making this information available for a great quantity of users, with stressed interactivity. This work shows the development of a system for digital images Compression with base on Huffman and Wavelets procedures of data storage and transmission in environments using digital images processing. It was developed on the C++ language under Windows environment. For results validation there were used standard images patterns of digital image Processing, as the Lena and Girl image, both on 128x128, 256x256 and 512x512 pixels resolutions, as well as tomographics images of soil and wood sample from tomograph of the Brazilian Agricultural Research Corporation.
Keywords: Processamento de imagens; Compressão de imagens; Descompressão de imagens; Wavelets (Matemática); CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO